2014
DOI: 10.2500/ajra.2014.28.4008
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Peak Inspiratory and Expiratory Flow Measurements for Assessing Nasal Obstruction in Allergic Rhinitis

Abstract: Among nasal peak flow measurements, PEFI is the most appropriate objective tool for assessing nasal patency in AR. Peak flows can indicate underlying mucosal inflammation and are more sensitive to assess score changes after treatment than cross-sectional assessment at the initial visit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…), by means of a portable flow meter such as the Youlten peak flow meter (Clement Clark International), and/or expiration (PNEF), by means of a Wright's mini peak flow meter (Clement Clark International) . PNIF and PNEF are closely correlated , both of them have been demonstrated to be valid for the measurement of nasal flow , and are well tolerated by patients . Although inspiratory manoeuvres may cause alar collapse and thus valve insufficiency, and in few cases, when the nose is totally blocked, it is not possible to obtain a measurement , PNIF has some undoubtable hygienic advantages over PNEF .…”
Section: Objective Measurements Of Nasal Airflow and Patencymentioning
confidence: 99%
See 1 more Smart Citation
“…), by means of a portable flow meter such as the Youlten peak flow meter (Clement Clark International), and/or expiration (PNEF), by means of a Wright's mini peak flow meter (Clement Clark International) . PNIF and PNEF are closely correlated , both of them have been demonstrated to be valid for the measurement of nasal flow , and are well tolerated by patients . Although inspiratory manoeuvres may cause alar collapse and thus valve insufficiency, and in few cases, when the nose is totally blocked, it is not possible to obtain a measurement , PNIF has some undoubtable hygienic advantages over PNEF .…”
Section: Objective Measurements Of Nasal Airflow and Patencymentioning
confidence: 99%
“…PNIF has been successfully used for the evaluation of treatment in allergic rhinitis and its treatment both in adults and in children/adolescents . Studies have assessed the efficacy of intranasal corticosteroids in patients with NP using PNIF , showing a significant increase in PNIF which was accompanied by subjective improvement of nasal blockage, and by an associated reduction in nasal polyp size .…”
Section: Objective Measurements Of Nasal Airflow and Patencymentioning
confidence: 99%
“…This was expected because discrepancies among the clinical, physiologic, and inflammatory asthma control parameters were reported, 32-37 which stressed the importance to manage asthma based on the evaluation of these three key components. 38 In keeping with this, Kirtsreesakul et al 39 observed better correlations between nasal peak flow and mucociliary clearance time, a surrogate marker of underlying mucosal inflammation, than between nasal peak flow and symptom score, which stressed the importance of assessing the multifaceted nature of rhinitis. Because thresholds have not been determined to assign the degree of severity or control with this measurement, we propose that patient's personal best values be determined and control management should aim at maintaining an adequate score accordingly.…”
Section: Discussionmentioning
confidence: 86%
“…This method includes measurement of peak nasal expiratory flow (PNEF) and peak nasal inspiratory flow (PNIF) . Both PNEF and PNIF have shown good correlations with rhinomanometry and have been demonstrated to be valid for the assessment of an absolute value of nasal airflow . It is likely that the reversibility of both nasal peak flow techniques after decongestion could be used as a simple method for indirectly assessing the degree of underlying mucosal inflammation.…”
Section: Introductionmentioning
confidence: 99%